Acoustic Change Complex Evoked by Horizontal Sound Location Change in Young Adults With Normal Hearing - Fan, Zhi-Tong; Zhao, Zi-Hui; Sharma, Mridula; Valderrama, Joaquin T.; Fu, Qian-Jie; Liu, Jia-Xing; Fu, Xin; Li, Huan; Zhao, Xue-Lei; Guo, Xin-Yu; Fu, Luo-Yi; Wang, Ning-Yu; et al. (Frontiers in Neuroscience, 2022)
Acoustic Change Complex (ACC) is a Cortical Auditory Evoked Potential induced by a change of continuous sound stimulation. This study aimed to explore: (1) Whether the change of horizontal sound location can elicit ACC; (2) The relationship between the change of sound location and the amplitude or latency of ACC; (3) The relationship between the behavioural measure of localization, Minimal Audible Angle (MAA) and ACC. Thirty-six normal-hearing adults participated in this study. An 180° horizontal arc-shaped bracket with a 1.2 m radius was set in a sound field where participants sat at the centre. MAA was measured in a two-alternative forced-choice setting. The objective electroencephalography recording of ACC was conducted with location changed at four sets of positions, ±45°, ±15°, ±5° and ±2°. The test stimulus was a 125-6000 Hz broadband noise of 1 s at 60±2 dB SPL with a 2 s interval. The N1’-P2’ amplitudes, N1’ latencies and P2’ latencies of ACC under four positions were evaluated. The influence of electrode sites and the direction of sound position change on ACC waveform was analyzed with Analysis of Variance. Results suggested that (1) ACC can be elicited successfully by changing the horizontal sound location position. The elicitation rate of ACC increased with the increase of location change. (2) N1’-P2’ amplitude increased and N1’ and P2’ latencies decreased as the change of sound location increased. The effects of test angles on N1’-P2’ amplitude (F (1.91, 238.1) = 97.172, P < 0.001), N1’ latency (F (1.78, 221.90) = 96.96, P < 0.001), P2’ latency (F (1.87, 233.11) =79.97, P < 0.001) showed a statistical significance. (3) The direction of sound location change had no significant effect on any of ACC peak amplitudes or latencies. (4) Sound location discrimination threshold by ACC test (97.0% elicitation rate at ±5°) was higher than MAA threshold (2.08 ± 0.5°). The current study results show that though the ACC thresholds are higher than the behavioural thresholds on MAA task, ACC can be used as an objective method to evaluate sound localization ability. This has implications for clinical practice and evaluation of localization skills, especially for children.